2016
DOI: 10.1155/2016/7580731
|View full text |Cite|
|
Sign up to set email alerts
|

Kaempferol Attenuates Myocardial Ischemic Injury via Inhibition of MAPK Signaling Pathway in Experimental Model of Myocardial Ischemia‐Reperfusion Injury

Abstract: Kaempferol (KMP), a dietary flavonoid, has antioxidant, anti-inflammatory, and antiapoptotic effects. Hence, we investigated the effect of KMP in ischemia-reperfusion (IR) model of myocardial injury in rats. We studied male albino Wistar rats that were divided into sham, IR-control, KMP-20 + IR, and KMP 20 per se groups. KMP (20 mg/kg; i.p.) was administered daily to rats for the period of 15 days, and, on the 15th day, ischemia was produced by one-stage ligation of left anterior descending coronary artery for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
71
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 29 publications
4
71
1
Order By: Relevance
“…In contrast, treatment with KF reduced the serum cardiac markers due to decreased leakage of these markers into serum (Vishwakarma et al, 2018). The current study was supported by the previous reports, which indicated that KF treatment caused the decrease in cell damage and increase in cell integrity and thereby decreases the serum cardiac injury markers in ISO-induced cardiac toxicity in rats (Suchal et al, 2016). The results of the present study are also in agreement with reports of the earlier study which suggested that KF treatment decreased creatine kinase and LDH in MI-induced rats (Zhou, Ren et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, treatment with KF reduced the serum cardiac markers due to decreased leakage of these markers into serum (Vishwakarma et al, 2018). The current study was supported by the previous reports, which indicated that KF treatment caused the decrease in cell damage and increase in cell integrity and thereby decreases the serum cardiac injury markers in ISO-induced cardiac toxicity in rats (Suchal et al, 2016). The results of the present study are also in agreement with reports of the earlier study which suggested that KF treatment decreased creatine kinase and LDH in MI-induced rats (Zhou, Ren et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…In addition to these enzymes, GR and GST provide GSH to neutralize the toxic electrophiles (Giacco & Brownlee, 2010). The present study results are in par with previous studies, where reduced MDA levels with increased SOD, CAT, and GPx activity levels were observed in KF-treated ISO-induced cardiac toxicity in rats (Suchal et al, 2016). Recently, a few other studies showed that KF treatment reduced the LPO and bought back antioxidant enzymes like SOD, CAT, GPx, and GST in liver, kidney, and heart of diabetic rats (Al-Numair, Chandramohan, Veeramani, & Alsaif, 2015) and ISO-induced myocardial injury rats (Zhou, Ren et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Experimental studies have shown that the mitogen-activated protein kinase (MAPK) signaling pathway is involved in myocardial response to oxidative stress in several conditions [41-43]. MAPK includes four subfamilies, three of which have been well characterized: extracellular regulated kinase (ERK 1/2), c-jun N-terminal kinase (JNK), and p38-MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK includes four subfamilies, three of which have been well characterized: extracellular regulated kinase (ERK 1/2), c-jun N-terminal kinase (JNK), and p38-MAPK. After oxidative stress increase, MAPK downstream signaling may lead to myocardial hypertrophy and fibrosis [6, 41, 42, 44]. We therefore evaluated MAPK protein expression and observed that p-ERK and p-JNK were lower in AS-NAC than AS.…”
Section: Discussionmentioning
confidence: 99%